2003
DOI: 10.3106/mammalstudy.28.67
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation of Mus caroli from East and Southeast Asia based on mitochondrial cytochrome b gene sequences

Abstract: We examined intraspecific genetic variation in the mitochondrial cytochrome b gene (1140 bp) in the Okinawa mouse, Mus caroli (Rodentia, Muridae), from Okinawa, Taiwan, Hainan, Yunnan (southern China), Thailand, Vietnam and Java, to better understand their evolutionary history and human impact on dispersal and colonization by the mice. Populations from each of the seven localities had distinctive mitochondrial DNA sequences. The genetic distances, ranging from 0.015 to 0.045 (0.033 on average), were comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…Mus caroli and M. terricolor are both closely associated with open grassland or swampy habitat (including rice fields) and they show remarkably little variation in coat color across wide geographic ranges. In the case of M. caroli, this uniformity in external appearance contrasts with mtDNA evidence for considerable phylogeographic substructuring (Terashima et al, 2003;Shimada et al, 2007b). We postulate that the Mc1r gene in both of these taxa may be under even stronger functional constraint than other members of the group, due perhaps to their preferred, essentially open habitat.…”
Section: Pattern Of Substitutionscontrasting
confidence: 42%
“…Mus caroli and M. terricolor are both closely associated with open grassland or swampy habitat (including rice fields) and they show remarkably little variation in coat color across wide geographic ranges. In the case of M. caroli, this uniformity in external appearance contrasts with mtDNA evidence for considerable phylogeographic substructuring (Terashima et al, 2003;Shimada et al, 2007b). We postulate that the Mc1r gene in both of these taxa may be under even stronger functional constraint than other members of the group, due perhaps to their preferred, essentially open habitat.…”
Section: Pattern Of Substitutionscontrasting
confidence: 42%
“…Within Japan, M. caroli is distributed only on Okinawajima Island, where M. caroli and M. musculus are sympatric (Motokawa 1995, 2000; Motokawa et al 2003; Motokawa 2007; Iwasa 2015). Although it has been suggested that M. caroli on Okinawajima Island was introduced by humans (Motokawa 2000; Motokawa et al 2003), the population of M. caroli on Okinawajima Island exhibits genetic and morphological diversification from other populations of M. caroli (Motokawa et al 2003; Terashima et al 2003), suggesting that M. caroli in Okinawajima Island was established naturally, not by the human introduction (Terashima et al 2003). Shimada et al (2007), on the other hand, showed that Okinawajima Island population was closely related to the Laos lineage and supposed the Okinawajima Island population to have been introduced by humans.…”
mentioning
confidence: 99%